ANALISIS HADIS TENTANG AMAL BERKELANJUTAN DAN PENDIDIKAN SALAT BAGI ANAK - Abidin, Zainal (Hunafa: Jurnal Studia Islamika, 2008)
Islam asserts that whatever Â Muslims do in this world will give impacts to their life in the hereafter.Â  However, not all good deeds that muslims have performed so far in this world will always give incessant rewards, particularly for the deceased, except for three things as stated in the Prophetic hadÃ®th: sï¬adaqah jÃ¢riyyah (charity), beneficial knowledge for others, and good descendants who always pray for them. These categories are still debated by some scholars. Therefore, this paper is intended to study this hadÃ®th in order to reveal its validity.Kata Kunci: hadis, amal berkelanjutan, Â Â pendidikan salat, Â hujjah Â